Advances in food and nutrition research : volume 65 : marine medicinal foods: implications and application - animals and microbes - Kim, Se-Kwon (Advances in food and nutrition research, 2012)
This volume on medicinal foods from the sea narrates the bioactive principles of various marine floral (vertebrate and Invertebrate), faunal (Macro and Micro algal) and microbial sources. Contributions from eminent scientists worldwide explain about the latest advance implications in the development and application of marine originated functional foods, as potential pharmaceuticals and medicines for the benefit of humankind by meeting the present nutraceutical demands